2007
DOI: 10.1017/s1742170507001755
|View full text |Cite
|
Sign up to set email alerts
|

An alternative way to evaluate the environmental effects of integrated pest management: Pesticide risk indicators

Abstract: This study examines whether pesticide risk indicators can be used to evaluate the environmental effects of pesticide applications within integrated pest management (IPM) projects. Pesticide risk indicators, commonly used in European countries, are mathematical equations that consider data inputs such as application rates, toxicity levels of a pesticide's active ingredient, meteorological data, the soil characteristics of farm fields, and other information to generate potential risk scores for pesticide applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 8 publications
0
36
0
1
Order By: Relevance
“…If farmer used many kind of pesticide, then EIQ Practical is the sum of EIQs of all pesticides used. An alternative way to evaluate the environmental effects of integrated pest management is use of pesticide risk indicators [9]. These indicators are: the synoptic evaluation model for plant protection agents (SYNOPS) indicator from Germany, the multi-attribute toxicity from the United States and the environmental impact quotation from the United States.…”
Section: Calculating Eiq Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…If farmer used many kind of pesticide, then EIQ Practical is the sum of EIQs of all pesticides used. An alternative way to evaluate the environmental effects of integrated pest management is use of pesticide risk indicators [9]. These indicators are: the synoptic evaluation model for plant protection agents (SYNOPS) indicator from Germany, the multi-attribute toxicity from the United States and the environmental impact quotation from the United States.…”
Section: Calculating Eiq Indexmentioning
confidence: 99%
“…According to EIQ values list updated on Cornell University's website [9], we have collected and classified an EIQ Theory in study area as shown in Table 5 Using equation (1) with data collected through survey we can calculate EIQ Practical on fields of the 3 studied communes. The EIQ result shows that: My Dong (closed dyke) has EIQ value up to 167.02, Phu Dien (semi-dyke area) at 145.43, but Truong Xuan (non-embankment) is only 54.03, which indecates that the closed dyke and semi-dyke areas have EIQ much higher than non-embankment areas especially, the close dyke area has EIQ value over the safety limit set by Cornell University, 150.…”
Section: Evaluating Pesticide Risk Through Environmental Impact Quotimentioning
confidence: 99%
“…Determination of the factors that affect the magnitude of pesticides impact is important to note. Determining factors are aiming to get a real relationship between the concentration of pesticide exposure to human impact is included in order to discover solutions of impact prevention [8]. In this study, a factor that is observed is the uptake of organophosphat and carbamate pesticides in the body's absorption of farmers, working experience, age, nutritional status (BMI) and smoking habits.…”
Section: Exposure Analysismentioning
confidence: 99%
“…Pesticide use raises significant concerns over impacts on health [2][3][4][5][6][7] and the environment [8][9][10][11][12]. Furthermore, we cannot address the challenges to sustainability posed by synthetic pesticides by simply switching to the application of natural pesticides, because the same concerns apply to them [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%